Finance and cluster-based industrial development in China - Ruan, Jianqing; Zhang, Xiaobo (International Food Policy Research Institute, 2008)
The traditional literature emphasizes the causal role of finance in promoting industrial growth. China's rapid industrialization over the past several decades, which has occurred in the absence of well-functioning financial markets, seems to defy the conventional wisdom. By studying a cashmere sweater cluster in China, this paper argues that rural industrial clustering, as a new business model, lowers the entry barriers of initial capital investment through the division of labor. Within these clusters, enterprises can often acquire trade credits from upstream or downstream firms and obtain informal financing from friends and relatives, and use these funds to mitigate constraints of working capital. These findings help explain China's rapid industrialization in the absence of an efficient financial market.